2021
DOI: 10.3389/fphys.2021.719753
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial BKCa Mediates the Protective Effect of Low-Dose Ethanol Preconditioning on Oxygen-Glucose Deprivation and Reperfusion-Induced Neuronal Apoptosis

Abstract: Ischemia-reperfusion (I/R) injury contributes to the morbidity and mortality of ischemic strokes. As an in vitro model, oxygen-glucose deprivation and reperfusion (OGD/R) exposure induces neuronal injury. Low-dose ethanol preconditioning (EtOH-PC) was reported to alleviate neuronal apoptosis during OGD/R. However, whether the mitochondrial BKCa (mitoBKCa) channel is involved in the neuroprotective effect of EtOH-PC during OGD/R is not clearly defined. This study attempts to explore the mediation of the mitoBKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…BKca channel opener can mitigate neuronal depolarization; the elevation of intracellular Ca 2+ and neurotransmitter release after stroke and activation of BKca channel exerts potent neuroprotection [ 50 , 51 ]. Additionally, opening the mitochondrial BKca channel increased the mitochondrial membrane potential and attenuated the oxygen-glucose deprivation and reperfusion-induced upregulated cleaved caspase3 and neuronal apoptosis [ 52 ]. A previous study confirmed that BKca channel opener reduced the production of ROS in isolated rat brain mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…BKca channel opener can mitigate neuronal depolarization; the elevation of intracellular Ca 2+ and neurotransmitter release after stroke and activation of BKca channel exerts potent neuroprotection [ 50 , 51 ]. Additionally, opening the mitochondrial BKca channel increased the mitochondrial membrane potential and attenuated the oxygen-glucose deprivation and reperfusion-induced upregulated cleaved caspase3 and neuronal apoptosis [ 52 ]. A previous study confirmed that BKca channel opener reduced the production of ROS in isolated rat brain mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In models of focal cerebral I/R and OGD/R, ischemic preconditioning promoted cell survival by inhibiting I/R-induced reduction of the ER (endoplasmic reticulum)-located calcium sensor STIM1 (stromal interacting molecule 1) and plasma membrane channel ORAI1, blocked by silencing of STIM1 or ORAI1 [ 35 ]. Moderate ethanol preconditioning reduced apoptosis elicited by OGD/R or I/R by elevating the expression of large conductance calcium-activated potassium channels (BK Ca ) [ 137 , 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPTP reflects the structure and function of the mitochondria and it is located between the inner and outer membranes of the organelle (65). The lipid oxidative stress damage to the mitochondrial membrane leads to the abnormal opening of MPTP, which cannot maintain the normal potential difference of the inner membrane, while the oxidative phosphorylation on the inner membrane cannot proceed smoothly (66,67). The cytochrome C oxidase is also known as respiratory chain complex IV and it is embedded in the bilayer lipid membrane of the inner mitochondrial membrane (68).…”
Section: Discussionmentioning
confidence: 99%